Aplicação da lignina da palha do milho como polímero condicionante no desaguamento do lodo de estação de tratamento de esgoto - Vieira, Rogério Martins (Universidade Federal de São Carlos, 2020)
Wastewater treatment represents an important stage of basic sanitation and the conditioning of the generated sludge is a major challenge, due to high operating costs. In this sense, the use of natural conditioners from agro-industrial residues that assist this process becomes a promising alternative. The goal of this work was to evaluate the application of corn straw lignin as a conditioning polymer in the dewatering of sludge from a Wastewater Treatment Plant. The lignin samples were extracted by soda pulping, with NaOH, and the Klason method, and later characterized using the Fourier Transform Infrared (FTIR), 1H Nuclear Magnetic Resonance (1H NMR), Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray Spectroscopy (EDS), UV-Visible Spectroscopy and Thermogravimetric Analysis (TGA). The lignin samples obtained by the Klason method were applied to the sludge to evaluate its dewatering. The highest yield of lignin obtained was 2.22% for the soda pulping and 24.6% for the Klason method. From the characterization, a typical chemical composition of lignins was observed, with the presence of hydroxyl, aromatic, methoxy and aliphatic groups. Its morphology was predominantly straight and amorphous. In its elemental composition, in addition to carbon and oxygen, the elements sodium and chlorine were identified as residues of the extractive process. The thermal stability of the sample was also observed even at high temperatures. After sludge conditioning, lignin had no influence on sludge dewatering, due to the insolubility in water and the low density of loads, which indicates the need for chemical modification of the lignin to act as a sludge conditioning agent.
Application of corn straw lignin as conditioning polymer in the dewatering of sludge from Wastewater Treatment Plant
Keywords: Lignina.; Palha do milho.; Polímero.; Condicionamento e desaguamento do lodo.; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS